Somatostatin analogues as antineoplastic drugs - Asendrych, Alicja; Deptała, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2003)
Somatostatin (SST) is a peptide synthesized in D-cells of pancreas. The effect of SST are thought to be mediated via specific SST receptors (SSTRs) which is widely represented on cells of normal tissues and altered by the disease. There is a known use of somatostatin analogues (SSTA) in the management of endocrine disorders such as acromegaly and symptoms caused by gastrointestinal neoplasms of endocrine organs for example gastrinoma, VIPoma and carcinoid tumor. Because of SSTRs are expressed on many neoplastic cells there are many trials evaluating SSTA in the treatment of neoplastic tumors. The main and best known of SSTA is octreotide. The first antiproliferative effects of SSTA in men were reported in patients suffering from neuroendocrine tumours who underwent treatment with the SSTA mainly with intention of achieving symptomatic palliation. There were hoted benefits from the combination of noted some of SSTA with gemcytabine in pancreatic cancer, with interferon alpha in endocrine tumors and with antiestrogenic agents in breast cancer. SSTA have wide therapeutic index and mild side effects. In some trials, prolonged survival was observed, so further clinical studies are needed, but there was no tumor regression observed in any trial. The future of SSTA is in their combination with other antineoplastic drugs such as gemcytabine, interferon alpha, tamoxifen. A new approach is the use of SSTA labeled with isotope for the treatment of tumors rich in SSTRs. Reported trials provide a rationale for further clinical studies, but still do not justify the use SSTA as sole antineoplastic drugs.